PENGARUH CHARACTER STRENGTHS DAN SPIRITUALITAS TERHADAP KESEHATAN MENTAL REMAJA KORBAN BULLYING DI SUMBAWA - jun naidin Junaidin; Roni Roni Hartono (UIN Sultan Aji Muhammad Idris Samarinda, 2026)
This study aims to investigate the influence of character strengths and spirituality on the mental health of adolescents who are victims of bullying in Sumbawa. Bullying is a social problem that has a serious impact on the psychological well-being of adolescents, leading to anxiety, depression, stress, low self-esteem, and social adjustment disorders. This study employs a quantitative approach using an ex post facto research design. The study sample consisted of 250 adolescents who were victims of bullying, selected using purposive sampling. Data collection was carried out using the character strengths scale, the spirituality scale, and the mental health scale, all based on the Likert scale model. Data analysis was performed using multiple linear regression with the aid of SPSS version 30. The results indicate that character strengths and spirituality have a positive and significant effect on the mental health of adolescents who are victims of bullying, with a significance level of 0.000 < 0.05. The coefficient of determination (R²) value of 0.313 indicates that character strengths and spirituality contribute 31.3% to the mental health of adolescents who are victims of bullying, whilst the remainder is influenced by other factors outside the scope of this study. The conclusion is that the higher the character strengths and spirituality possessed by adolescents who are victims of bullying, the better their mental health.